2015
DOI: 10.4172/2167-1168.1000244
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control Demands and Job Strain in Nursing and Care: The Moderating Role of Boundary Conditions

Abstract: Recent theoretical developments and findings in basic research suggest that, self-control demands are a unique job stressor. A series of studies among healthcare workers are reported corroborating this view. The results of literature review show that different forms of self-control demands such as impulse control, resisting distractions, overcoming inner resistances contribute significant portions of unique variance to the prediction of various indicators of job strain and interact with other forms of self-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Meanwhile, self‐control is a unique factor that is often overlooked in job stressor. The relationship between self‐control needs and work pressure, emotional organisational commitment and self‐control capacity can help healthcare staff to counter the adverse effects of coping with self‐control needs)Schmidt, ). Besides, Por, Barriball, Fitzpatrick, and Roberts () found that resilience promotion helps nurses and nursing students manage stressors as well as their emotions and improve their subjective well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, self‐control is a unique factor that is often overlooked in job stressor. The relationship between self‐control needs and work pressure, emotional organisational commitment and self‐control capacity can help healthcare staff to counter the adverse effects of coping with self‐control needs)Schmidt, ). Besides, Por, Barriball, Fitzpatrick, and Roberts () found that resilience promotion helps nurses and nursing students manage stressors as well as their emotions and improve their subjective well‐being.…”
Section: Discussionmentioning
confidence: 99%